(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2019)
In looking back to the SEA’s origins and imagining forward into our future, this transcript of a keynote talk explores two key concerns – relatedness and responsibility – in an attempts to illuminate just what might be existential about existential therapy and why it might just be worth all our efforts to ensure its continuing existence.